2020
DOI: 10.1111/iwj.13490
|View full text |Cite
|
Sign up to set email alerts
|

The effect of continuous diffusion of oxygen treatment on cytokines, perfusion, bacterial load, and healing in patients with diabetic foot ulcers

Abstract: To evaluate continuous diffusion of oxygen therapy (CDO) on cytokines, perfusion, and bacterial load in diabetic foot ulcers we evaluated 23 patients for 3 weeks. Tissues biopsies were obtained at each visit to evaluate cytokines and quantitative bacterial cultures. Perfusion was measured with hyperspectral imaging and transcutaneous oxygen. We used paired T tests to compare continuous variables and independent T tests to compare healers and nonhealers. There was an increase from baseline to week 1 in TGF‐β (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
(71 reference statements)
1
15
0
Order By: Relevance
“…Interestingly, they did not find a significant increase in VEGF expression in those patients treated with HBOT. Similar increases in VEGF and other cytokines in healers vs. non-healers were reported more recently in patients treated with CDO [14,31].…”
Section: Topical Oxygen Effect On Wound Healing-the Evidencesupporting
confidence: 83%
“…Interestingly, they did not find a significant increase in VEGF expression in those patients treated with HBOT. Similar increases in VEGF and other cytokines in healers vs. non-healers were reported more recently in patients treated with CDO [14,31].…”
Section: Topical Oxygen Effect On Wound Healing-the Evidencesupporting
confidence: 83%
“…Results showed significant increases in growth factors, cytokines and transcutaneous oxygen pressure measurement levels after application of CDOT. Growth factors significantly increased from 280% to 820% of base levels in the first week and decreased in subsequent weeks [50] (Figure 1). Cytokines increased significantly (up to 680% compared to baseline levels) in the first two weeks and then decreased.…”
Section: Molecular Biomarkers In Growth Factor Signaling Transductionmentioning
confidence: 97%
“…In a study using supplemental oxygen at a rate of 4 L/min through nasal cannula for 12 h a day for 3 days, it was found that three times as much collagen was deposited in patients with well-perfused and oxygenated wounds compared with those with lower oxygenation and perfusion scores [54]. A separate study using direct topical oxygen on chronic diabetic foot ulcers showed significant increases in the expression of genes associated with collagen production (TGF-β, VEGF and IL-6) during weekly follow-up visits after application of CDO in patients with diabetic foot ulcers [50].…”
Section: Collagen Formationmentioning
confidence: 98%
See 1 more Smart Citation
“…9 Applied oxygen to wounds has proven to stimulate collagen synthesis, matrix deposition, keratinocyte differentiation, and fibroblast migration, through cytokines and growth factors activated by the release of reactive oxygen species (ROS), which also play an antibacterial role in the wound site. [9][10][11] Moreover, oxygen may promote angiogenesis, and the process itself could be more efficient if the cutaneous tissue is sufficiently maintained oxygenated. 9 , 12 Therefore, the level of transcutaneous oxygen could be a determinant factor of excessive SF 13 .…”
Section: Introductionmentioning
confidence: 99%